Peran Heuristik dalam Mengembangkan Kerangka Ilmu Pengetahuan Modern - Zanki, Amir Basari; Fahrul, Moh; Pahude, Jupriadi J.; Thahir, Lukman S; Nurhayati, Nurhayati; Zanki, Harits Azmi; Indriani, Indriani (Universitas Muhammadiyah Magelang, 2026)
This study examines the role of heuristics in developing the framework of modern scientific knowledge through a library research method utilizing twenty journal articles published within the last decade. The central question addressed concerns how heuristics function as both cognitive and methodological mechanisms shaping reasoning patterns, theory construction, and scientific problem-solving. This study employs a library research approach by systematically reviewing relevant scientific articles through structured processes of searching, screening, and examining indexed academic literature. The data were analyzed using content analysis and thematic synthesis to identify key concepts, thematic trends, and the relationships among arguments presented across the selected studies. The findings reveal that heuristics operate not merely as simplification strategies but as epistemological foundations enabling the emergence of new conceptual models, theoretical revisions, and scientific innovation. Principles such as analogy, abstraction, concept mapping, and pattern-based reasoning contribute significantly to research efficiency and strengthen the validity of scientific inference. The study concludes that the modern scientific knowledge framework is inherently adaptive and evolves through continuous heuristic processes. Its implications include reinforcing the theoretical basis of modern epistemology, enhancing heuristic integration within methodological design, and emphasizing the need to incorporate heuristic competencies in education and future research development.